Definitions of the Terms Open, Distance, and Flexible in the Context of Formal and Non-Formal Learning - Simon Paul Atkinson (Flexible Learning Association of New Zealand, 2023)
This opinion piece seeks to define and contextualise educational terms that are used, and appear to be misused, in contemporary academic literature and practice. It aims to explore the concept that these three words, open, flexible, and distance, fall into the categories of policy, mode of learning, and models of delivery. In the context in which the global educational community across all sectors adapts to new forms of learning, it is essential that practitioners agree on the terminology. Words have definitions, but they also have technical meanings and daily, commonplace, uses that sometimes defy those dictionary definitions. Words sometimes become symbolic, they are adopted by a specific community to cover a range of "sins", and this use serves to normalise or induct new users into that community. The ability to twist and bend definitions to suit a specific context, to appeal to policy makers or funders, relies on some malleability, some ambiguity, of definitions. In the context of Boyer's definition of the integration of research (Boyer, 1997), the purpose of this piece is to enable colleagues to decide how to best define and deploy existing, and validate new terminology.